2020
DOI: 10.1186/s12890-020-01333-1
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA0001859, a new diagnostic and prognostic biomarkers for COPD and AECOPD

Abstract: Background Dysregulation of circRNAs has been reported to be functionally associated with chronic obstructive pulmonary disease (COPD). The present investigation elucidated the potential role of CircRNA0001859 in regulating chronic obstructive pulmonary disease acute (COPD) and Acute Exacerbation of COPD (AECOPD). Methods Mice model of COPD was established to screen and verify the dysregulated expression of CircRNA0001859. Fluorescence in situ hybridization (FISH) and quantitative real-time PCR (qRT-PCR) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…16 In addition, a recent study found that circRNA0001859 was down-regulated in lung tissue of mice and may be a potential biomarker for the treatment of COPD. 17 Moreover, one previous study demonstrated that autophagy-associated protein levels of PBMCs in COPD patients were increased and were correlated with FEV 1 % predicted values and circulating levels of cytokines. 15 However, there are still few related studies in this field, and further investigations will be required to better understand this field.…”
Section: Discussionmentioning
confidence: 97%
“…16 In addition, a recent study found that circRNA0001859 was down-regulated in lung tissue of mice and may be a potential biomarker for the treatment of COPD. 17 Moreover, one previous study demonstrated that autophagy-associated protein levels of PBMCs in COPD patients were increased and were correlated with FEV 1 % predicted values and circulating levels of cytokines. 15 However, there are still few related studies in this field, and further investigations will be required to better understand this field.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence long suggests that lncRNAs, miRNAs, and circRNAs along with mRNAs could massively involved in the progression of many diseases, with some of them being identified as potentially suitable biomarkers [ 32 , 33 ]. However, there is only a limited number of studies for the universal investigations on the differentially expressed RNAs of COPD, especially circRNAs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current reports demonstrated that circ_0001859 could be employed as a diagnostic and prognostic biomarker based on its dysregulation in CS-treated lung tissues of mice and peripheral blood of patients with COPD as well as the analysis of receiver operating characteristics (ROC) curve. 23 Duan et al analyzed the expression profiles of circRNAs and mRNAs, and demonstrated that circRNAs played vital roles in COPD process via regulating the immune balance and inflammatory responses. 24 In mechanism, Ma and his colleagues explained that circ_0061052 implicated in epithelial–mesenchymal transition of CSE-induced airway remolding by controlling forkhead box C1/snail pathway through binding to miR-515-5p.…”
Section: Discussionmentioning
confidence: 99%